Prognostic significance of atypical/hybrid forms of EpCAM+CD45+ cells in the blood of patients with endometrial cancer - E. V. Kaigorodova; I. S. Zavaruev; A. L. Chernyshova; M. Yu. Grishchenko (Опухоли женской репродуктивной системы)
Background. Endometrial cancer occupies a leading position in the structure of oncogynecological pathology. According to modern literature, circulating tumor cells, which represent a heterogeneous population, participate in the processes of recurrence and metastasis. Moreover, tumor cells can form hybrid forms with blood cells, increasing their malignancy.Aim. To conduct a comparative characterization of the features of the occurrence of atypical/hybrid forms of EpCAM+CD45+ cells in the blood of patients with endometrial cancer before and after surgery, and to assess their prognostic significance.Material and methods. The prospective study NCT04817501 included 55 patients with newly diagnosed T1a-2N0M0 stage endometrial cancer, average age 57.8 ± 1.7 years, who were admitted for treatment at the Research Institute of Oncology, Tomsk National Research Medical Center of the Russian Academy of Sciences and/or Tomsk Regional Oncological Dispensary. At the same time, metastases and cancer recurrences were found in 11 patients out of 55 patients after 4–5 years of follow-up after treatment. The material for the study was stabilized EDTA venous blood taken from patients before surgical treatment of the tumor and on the third day after treatment. The presence of atypical/hybrid forms of EpCAM+CD45+ cells in blood serum was determined by multicolored flow cytometry using monoclonal antibodies to CD45 and EpCAM molecules labeled with various fluorochromes.Results. When comparing the frequency of occurrence of atypical/hybrid EpCAM+CD45+ cells in patients with endometrial cancer before surgery and on the third day after surgery, no differences were found. Comparing the frequency of occurrence of atypical/hybrid forms of EpCAM+CD45+ cells in patients with endometrial cancer with hematogenous metastases and relapses and in patients with endometrial cancer without hematogenous metastases and relapses, it was found that in the blood of patients with endometrial cancer before surgery, with developed hematogenous metastases and relapses after treatment, EpCAM+CD45+ cells are more common (p = 0.03). It was found that the concentration of EpCAM+CD45+ cells in patients with established relapses and metastases of 125 (120;387) cells/ml is higher (p = 0.022) than in patients without these complications of 30 (0;220) cells/ml. During the ROC analysis, it was found that the best cut-off point for the model is the value of 80 cells/ml. The sensitivity of the model is 81.8 %, the specificity is 67.7 %. The indicator of the area under the ROC curve was 0.733.Conclusion. The number of atypical/hybrid forms of EpCAM+CD45+ cells before treatment is associated with the risk of relapses and hematogenous metastases in patients with endometrial cancer.